2013
DOI: 10.1155/2013/123838
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Studies of Various Sizes of Gold Nanoparticles and Their Cellular Localizations

Abstract: Gold nanoparticles (GNPs) are widely used in biological and clinical applications due to their favorable chemical and optical properties. GNPs can be used for drug delivery to targeted cells. In addition, GNPs serve as ideal probes for biological and cell imaging applications. Recent studies indicate that the size diversity of GNPs plays an important role in targeting cellular components for biomedical applications. In this study, we conducted a series of studies using different sizes of gold nanoparticles, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 38 publications
5
31
0
Order By: Relevance
“…In our findings, the development of gold nanostructures definite in TEM figures, in which morphological individuality provides high-density AuNPs shaped by the Strychni Semen extract. Previous studies confirm the size and shape of gold nanoparticles performed by TEM studies in Hep-2 cells, where the TEM examination of all gold nanoparticles was reliable with the ascending like 3, 11, 27, and 51 nm [30]. Many studies support our data like the TEM investigated the phase and contrivance of the cellular incorporations of protein-covered gold nanoparticles by means of the HeLa cell lines [31].…”
Section: Discussionsupporting
confidence: 87%
“…In our findings, the development of gold nanostructures definite in TEM figures, in which morphological individuality provides high-density AuNPs shaped by the Strychni Semen extract. Previous studies confirm the size and shape of gold nanoparticles performed by TEM studies in Hep-2 cells, where the TEM examination of all gold nanoparticles was reliable with the ascending like 3, 11, 27, and 51 nm [30]. Many studies support our data like the TEM investigated the phase and contrivance of the cellular incorporations of protein-covered gold nanoparticles by means of the HeLa cell lines [31].…”
Section: Discussionsupporting
confidence: 87%
“…The 5 nm particles showed much higher cytotoxicity than the 13 nm particles, whether in normoxic or in hypoxic conditions, which is consistent with a previously reported trend. 8,10,13 In addition, only a slightly reduced proliferation was detected in the hypoxic group compared with the corresponding normoxic group (Figure 2), which may be correlated with the amount of GNPs taken up by hypoxic cells because more GNPs localizing inside cells could induce greater cytotoxicity.…”
Section: Discussionmentioning
confidence: 96%
“…Among them, some groups reported that the extent of the toxic nature of these particles depended on the different diameter sizes, [8][9][10][11][12][13] the modifications, 14,15 and the surface functional attachments 16,17 of the GNPs. In the articles, GNPs were reported to induce various cellular responses, such as necrosis, autophagy, apoptosis, altered gene expression, cell cycle disruption, and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshida et al reported that amorphous nanosilica causes toxicity in the human cell, both by increasing ROS formation and by damaging DNA [111,112]. Besides, only in the evaluation based on its size, the smaller the nanoparticles, the more toxic it is to the organs [113]. Studies were reported that wire-shaped nanomaterials cause DNA damage and toxic effects through ROS production [114].…”
Section: Toxicity Mechanisms Of Nanoparticlesmentioning
confidence: 99%